Pelestarian Kesenian Tradisional Gondang Buhun di Kampung Adat Kuta oleh Pemerintah Desa Karangpaningal Kecamatan Tambaksari Kabupaten Ciamis - Kurnia Fitriani; Irfan Nursetiawan; Otong Husni Taufik (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This research is motivated by the problem in the Preservation of Gondang Buhun Traditional Arts in Kuta Traditional Village, Karangpaningal Village. This study uses a descriptive method with a qualitative approach with primary data sources in the form of interview results from 6 informants consisting of 1 village, 1 village official, 1 village elder, 1 person from the Gondang Buhun art administrator, 1 member of the Gondang Buhun art, 1 person, 1 community/community leader. Secondary data is in the form of relevant documentation. The data collection technique consists of observation, interviews with the stages of data reduction analysis, data presentation, and conclusion drawn. The results of the study show that the Karangpaningal Village Government has a role in the preservation of Gondang Buhun's traditional arts, including the role of stabilizer through support for the sustainability of traditional events through Gondang Buhun performances. The role of innovators encourages the birth of creativity through the development of training patterns, the role of modernizers facilitates it, the role of pioneers to be the main actors who initiate conservation initiatives through policy support, village budget allocation, and the role of self-implementers to provide instructions or directions. The obstacles found are the lack of regeneration of young artists, limited funds, and lack of promotion which have an impact on the decline of the existence of Gondang Buhun among the younger generation. Efforts that have been made are to support preservation through the provision of village budgets, training procurement, and support art performances at various traditional and state events.